Severe Lumbar Disability Is Associated With Decreased Psoas Cross-Sectional Area in Degenerative Spondylolisthesis. Issue 7 (October 2018) - Wagner, Scott C.; Sebastian, Arjun S.; McKenzie, James C.; Butler, Joseph S.; Kaye, Ian D.; Morrissey, Patrick B.; Vaccaro, Alexander R.; Kepler, Christopher K.
Study Design: Retrospective cohort. Objectives: Alterations in lumbar paraspinal muscle cross-sectional area (CSA) may correlate with lumbar pathology. The purpose of this study was to compare paraspinal CSA in patients with degenerative spondylolisthesis and severe lumbar disability to those with mild or moderate lumbar disability, as determined by the Oswestry Disability Index (ODI). Methods: We retrospectively reviewed the medical records of 101 patients undergoing lumbar fusion for degenerative spondylolisthesis. Patients were divided into ODI score ≤40 (mild/moderate disability, MMD) and ODI score >40 (severe disability, SD) groups. The total CSA of the psoas and paraspinal muscles were measured on preoperative magnetic resonance imaging (MRI). Results: There were 37 patients in the SD group and 64 in the MMD group. Average age and body mass index were similar between groups. For the paraspinal muscles, we were unable to demonstrate any significant differences in total CSA between the groups. Psoas muscle CSA was significantly decreased in the SD group compared with the MMD group (1010.08 vs 1178.6 mm 2, P = .041). Multivariate analysis found that psoas CSA in the upper quartile was significantly protective against severe disability ( P = .013). Conclusions: We found that patients with severe lumbar disability had no significant differences in posterior lumbar paraspinal CSA when compared with those with mild/moderate disability. However, severely disabled patients had significantly decreased psoas CSA, and larger psoas CSA was strongly protective against severe disability, suggestive of a potential association with psoas atrophy and worsening severity of lumbar pathology.